In Vitro and In Vivo Antifungal Activity of Clove (Eugenia caryophyllata) and Pepper (Piper nigrum L.) Essential Oils and Functional Extracts Against Fusarium oxysporum and Aspergillus niger in Tomato (Solanum lycopersicum L.) - Laila Muñoz Castellanos; Nubia Amaya Olivas; Juan Ayala-Soto; Carmen Miriam De La O Contreras; Miriam Zermeño Ortega; Fabiola Sandoval Salas; Leon Hernández-Ochoa (International Journal of Microbiology)
In this study, hydrodistillation was used to obtain essential oils (EOs) from pepper (Piper nigrum L.) and clove (Eugenia caryophyllata) and co-hydrodistillation (addition of fatty acid ethyl esters as extraction co-solvents) was used to obtain functional extracts (FEs). Antifungal activity of EOs and FEs was evaluated by determination of minimum inhibitory concentration (MIC) against Fusarium oxysporum and Aspergillus niger. The results showed that pepper (Piper nigrum) and clove (Eugenia caryophyllata) essential oils and their functional extracts are effective in vitro at concentrations from 400 to 500 ppm after 10 days of culturing. The essential oils and functional extracts were used on tomato fruit samples at three different concentrations: 350, 400, and 450 ppm5. Clove essential oil reduced the growth of Aspergillus niger from 50% to 70% and Fusarium oxysporum to 40%. The functional extracts (FEs) of clove and pepper, mixed with ethyl decanoate (FEs-C10), were the best combination for protecting the tomato fruit in vivo against both phytopathogenic fungi. Gas chromatography-mass spectrometry (GC-MS) was used to identify eugenol as the principal compound in clove oil and limonene, sabinene, and β-caryophyllene in pepper oil.